Temporary and Permanent Immigration under Unionization - Kondoh Kenji (European Regional Science Association (ERSA), 2004)
This paper investigates permanent and temporary immigration and remittance under the coexistence of unionized and non-unionized manufacturing firms in a two-sector economy. The impacts of immigration as well as remittance on respectively wages, employment, the union-nonunion wage gap and national welfare are analyzed. It is found that permanent immigration brings positive effects on most variables (except the competitive wage), but enlarges the wage gap and causes income redistribution. The effects of temporary immigration diverge depending on which sector immigrants are allowed to work in and which good is remitted more heavily. In particular, if temporary immigrants work in manufacturing only, then all wages and the union-nonunion wage gap fall. JEL Classification Numbers: F22, J51 Keywords: Temporary and Permanent Immigration, Labor Unions, Remittance, Wages
Keywords: F22; J51; 330; Temporary and Permanent Immigration; Labor Unions; Remittance; Wages